Climate crisis attitudes among financial professionals and climate experts - Elisabeth Gsottbauer; Michael Kirchler; Christian König-Kersting (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
Climate change constitutes one of the major challenges to humankind in the 21st century. To address this crisis, it is necessary to transform the economy and reduce greenhouse gas emissions. The finance industry has the potential to play a central role in this transformation by implementing sustainable investment and financing policies. We document climate mitigation preferences and attitudes toward the climate crisis of finance professionals - the key protagonists on financial markets - and climate experts - the key protagonists providing scientific findings. We use an incentivized choice experiment to measure the willingness to forgo individual payout to curb greenhouse gas emissions and survey participants to elicit their attitudes and beliefs toward the climate crisis. To learn how well both groups understand each other, we also ask participants what they believe the other stakeholder group believes. Our results provide suggestive evidence that finance professionals have a lower willingness to curb greenhouse gas emissions, measured through incentivized indifference valuations of carbon offsets, and are also less concerned about climate change compared to climate experts. Additionally, we find that the motivations and priorities of the two groups in addressing the climate crisis differ, with finance professionals being more driven by economic and reputational considerations and climate experts prioritizing the ecological andsocial consequences of the crisis. Finally, we find that finance professionals are less supportive of a carbon tax. Our findings have implications for policy and communication efforts,highlighting the importance of financial incentives and reputational concerns in motivating finance professionals to address the climate crisis.
Keywords: 330; Climate crisis; climate policy; beliefs; experiment; finance